Same Same but Different? Gender, sex work, and respectability politics in the MyRedBook and Rentboy closures - Majic, Samantha (Anti-Trafficking Review, 2020)
Among the many policies implemented to eradicate trafficking in the sex industry, US government agencies have targeted online platforms that market and facilitate sex work. In this paper, I consider two instances of this activity: the Federal Bureau of Investigation’s 2014 raid and subsequent closing of MyRedbook.com, and the Department of Homeland Security’s 2015 raid and closing of Rentboy.com. Drawing from a qualitative-interpretive analysis of the media coverage of these raids, I show that the responses to them emphasised how the sites’ closures increased both men’s and women’s economic vulnerability, but the similarities largely ended there. Instead, I argue broadly that public responses to these events reflected and reinforced gendered notions of women’s vulnerability and men’s agency in the sex industry. While these responses may seem unsurprising, they are also potentially productive, calling into question the limits of respectability politics and signalling new solidarities in the struggle for sex worker rights.